Detection of Cryptosporidium parvum by modified acid-fast stain among cancer patients in Thi-Qar province - alsafi, Zahraa; AL-Aboody, Bassad (University of Thi-Qar Journal of Science, 2023)
Cryptosporidium parvum is a widespread opportunistic parasite belonging to the family Apicomplexa that completes its life cycle in a single host and is found frequently in immunocompromised persons, especially in patients with cancer. This research’s objectives were to determine the prevalence of Cryptosporidium parvum infection among cancer patients in the Thi-Qar Province of Iraq, using modified Ziehl-Neelsen (MZN) stain. This study included 300 stool samples, 200 of which were for patients with cancer and 100 were for healthy people (the control group). Based on the modified acid-fast stain, the results showed the rate of infection with Cryptosporidium parvum among cancer patients was 54.0% (108/200) compared to 30.0% (30/100) in the control group, and there were statistically significant differences between them .And the percentage of infection among cancer patients in males was higher than in females, but there were no significant differences between them, as the percentage was 57.14% and 52.03%, respectively. As for the age groups Cryptosporidium parvum it affects all age groups in different proportions. The study showed that the highest infection rate among the age groups reached ?60 years at a rate of 64.44%, and the lowest infection rate among the age group ?20 years at a rate of 35.71%. As for the number doses of chemotherapy the results showed that the infection rate was higher in patients who received half and more than half of the doses of chemotherapy, where the percentage of those who received 16-20 doses (64.0%)